Utilizing rice-husk waste as an effective weed control mulch for Holy Basil (Ocimum sanctum ) production in a tropical environment - Vivian Ogechi Osadebe; Uchenna Noble Ukwu; Nathaniel Dauda; Ifesinachi M Nwamba; Amos Ejike Ede; Anthony I Onah (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The growing adverse effects of agrochemicals on environmental health and safety warrant an examination of ecologically safe alternatives for weed control. The objective of this study was to determine the effect of rice-husk waste on the growth performance and weed management (WM) of Ocimum sanctum. Method: In a randomized complete block design with three replications, nine weed management (WM) methods were assessed. These methods included black, red, and transparent polyethylene mulches; rice-husk; sawdust; hoe-weeding at 30 days after transplanting (DAT); a one-time application of 0.2 kg/ha Haloxyfop-P at 30 DAT; daily weeding; and no-weeding. Data were collected on weed parameters and growth attributes of Ocimum sanctum. All data were subjected to analysis of variance. Results: The use of rice-husk mulch resulted in the most significant (p<0.05) increase in plant height (41.70 cm), leaf number (206.80), branch number (50.50), stem girth (2.76 cm), and leaf yield (7.15 t/ha) of Ocimum sanctum compared to the other weed control methods. It was comparable to black polyethylene (BP) in these traits except in leaf number where BP recorded a lower value (165.00). BP mulch was significantly more effective in weed suppression as it recorded the least number of broad leaves (0.00), sedges (0.00) weed biomass (0.00), and the highest weed control efficiency (WCE) (100%) at 10 WAT. The treatments ranked BP>Daily-weeding>Hoe-weeded>Rice-husk>Haloxyfop-PEHS>Red-polyethylene>Sawdust> Transparent-polyethylene>Control in WCE at 10 WAT. Conclusion: The study revealed that rice-husk mulch was the most effective in enhancing the growth and yield attributes of Ocimum sanctum, ranking fourth in weed control efficiency (WCE) at 72.60%, following black polyethylene (BP) mulch (100%), daily-weeding (96%) and hoe-weeded (95.7%).